Phase Composition and Microstructure of Zn Coated Press Hardening Steels for Direct Hot Stamping - Kučera, Vojtěch; Pert-Soini, Jaroslav; Vojtěch, Dalibor (Manufacturing Technology Journal, 2018)
Decarburization and oxidation occur during production of press hardening steels (PHS) used in automotive. Therefore, coatings are applied on the steel surface to prevent this. The most common Zn coatings have not been processable by available direct hot stamping technology ordinarily used to produce the PHS and have been replaced by Al-Si coatings. However, the Al-Si coatings have a negative impact on joining technologies and further processing. Recently, the modification of direct hot stamping, which enables process the PHS with Zn coatings, was introduced. We investigated the microstructure, phase composition and distribution of particular phases (SEM-EDS, XRD), as well as micro-hardness of the Zn coated PHS prepared by the modified direct hot stamping. The PHS revealed the coating with 25 ± 3 μm thickness and continuous interface consisting of α-Fe(Zn) solid solution, Γ and Γ1 intermetallic phases and zinc oxides enriched with manganese. The thorough description of the material is important in development of further processing steps such as joining technologies and corrosion resistance.
Keywords: Zn coating; press hardening steels; direct hot stamping; liquid metal embrittlement